MASALAH DAN HAMBATAN USAHA BISNIS - Ika Ulandari; Esa Sintia; Ulayya Fadhila (Adiba Aisha Amira, 2024)
Business problems refer to challenges or obstacles that interfere with the achievement of a business's goals and objectives, both internal and external. These problems can affect various aspects of operations, finance, marketing, human resources, and the company's competitiveness in the market. Proper identification of problems is essential so that business owners or managers can formulate effective strategies to overcome these obstacles. Types of business problems include financial, marketing, operational, human resources, competition, and legal and regulatory issues. In addition, obstacles in business can also be divided into two main categories, namely internal and external obstacles. Internal obstacles are related to resource constraints, weak management, and inefficient processes, while external obstacles include economic conditions, market competition, regulatory changes, and technological developments. Understanding these obstacles is crucial to designing strategic steps that can improve business performance and sustainability. This article aims to review the various problems and obstacles that are often faced by companies, and provide insight into how to manage and overcome these challenges to achieve success in the competitive business world.